Aligning OCL with Domain-Specific Languages to Support Instance-Level Model Queries - Kolovos, Dimitrios; Paige, Richard; Polack, Fiona (Electronic Communications of the EASST, 2007)
The Object Constraint Language (OCL) provides a set of powerful facilities for navigating and querying models in the MOF metamodelling architecture. Currently, OCL queries can be expressed only in the context of MOF metamodels and UML models. This adds an additional burden to the development and use of Domain Specific Languages, which can also benefit from an instance-level querying mechanism. In an effort to address this issue, we report on ongoing work on defining a rigorous approach for aligning the OCL querying and navigation facilities with arbitrary Domain Specific Languages to support instance-level queries. We present a case-study that demonstrates the usefulness and practicality of this approach.